Material Replenishment System For SMT Kitting - Ong, Xuan Zhi (Universiti Sains Malaysia, 2016)
Purpose – Surface Mounted Technology (SMT) requires hundreds of components in the electronics assembly process run in mass production. These components varying in sizes and costs have to be transferred from warehouse to an area for preparation, commonly known as kitting. Oversight in kitting leads to long material replenishment lead time, component lost, and overstocking at the kitting area. This case study aims to investigate the issue and to generate solutions in alignment of the lean manufacturing philosophies. Design/methodology/approach – This case study is based on the SMT kitting area and warehouse of an electronic production plant. The project is executed by an undergraduate manufacturing engineering student and several operation leaders over a period of ten weeks. The methodology implemented is a plan-do-check-act (PDCA) approach. The data is collected via time study, direct observation and informal interviews. Findings – A visual system was introduced to unveil delay at every stage of the material replenishment process between the SMT kitting area and the warehouse of the company. Research limitations/implications – The case study is conducted in a discrete manufacturing industry where the sources and concerns may be localized and handled differently elsewhere. Practical implications – A systematic approach is provided to practitioner to implement material replenishment system between the SMT kitting area and warehouse. The system promotes the replenishment lead time reduction, inventory reduction, SMT kitting area space expansion and waste elimination. Originality/value – The paper is a real case study of electronics component replenishment between kitting area and warehouse. This field has not been explored to a high degree. Keywords – Electronics assembly, PDCA, Lean Manufacturing, SMT, Kitting